Pemberdayaan Kelompok Masyarakat Desa Baddurih dalam Pelatihan Pengolahan Tepung Mangrove Subsitusi Tepung Terigu - Mohammad Taufiq Hidayat; Rahmawati Ardila (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Market demand for the availability of souvenirs typical of Madura with local wisdom is relatively high, so the business of processed fisheries and marine products, namely mangroves, can be the right choice to start a business in order to improve the economy of a creative community. To fulfill this, efforts to increase production are needed. The partner of this program is the “Alam Mangrove” group in Baddurih Village, Pademawu District. Partners have a strong desire for entrepreneurship, especially in fulfilling various types of wet and dry cake snacks where the flour is obtained from mangrove plants or marine and fishery products.  However, the limited variety of cakes from marine and fishery products is a separate problem faced by partners in the context of processing flour products to meet the needs of existing culinary businesses. Limitations in the processing of fishery products require careful thought in efforts to empower something that is productive to become a creative economy. This program is carried out using training and mentoring methods including training in product manufacturing and cultivation training in product marketing management while mentoring is carried out in training, marketing and financial analysis. In the mentoring phase, monitoring and evaluation will also be carried out to ensure the sustainability of the program. The output of this program is the increased production of fishery products from the fishermen's group in Lembung Village. Other outputs from this program are publications in Proceedings and national scientific journals with ISSN, e-ISSN and publications in mass media